Transforming a federal agency : management lessons from HUD's financial reconstruction - Dennis, Irving L. (John Wiley & Sons, Inc., 2022)
"Fixing the House shares former CFO of the U.S Department of Housing and Urban Development's lessons in management through the story of how he transformed the HUD's weak financial infrastructure in only a matter of years. After a 37-year career at Ernst & Young, Irving was pulled out of retirement and became the CFO of HUD where he led a financial transformation process that required surgical and tactical leadership and management to accomplish a complete transformation of the financial infrastructure. Fixing the House is not about making political statements. It is about the importance of bringing private-sector experience to the government. The book is written so that each chapter or section stands on its own and critical management learnings can be gathered from each chapter or section, without reading the entirety of the book. Topics include: HUD's state of affairs upon arrival (2016) How Irving approached the first 100 Days. The evaluation of governance, people, processes, and technology. The transformation process. Barriers to success. Making it sustainable upon a change in administration. Differences between the private-sector and government"--